A Comparative Study between A Protein Based Amorphous Formulation and Other Dissolution Rate Enhancing Approaches: A Case Study with Rifaximin - Xuezhi Zhuo; Maud Margrethe Brekstad Kjellin; Zarah Schaal; Tengyu Zhang; Korbinian Löbmann; Donglei Leng (MDPI AG, 2022)
Amorphous solid dispersions (ASDs) based on proteins as co-formers have previously shown promising potential to improve the solubility and bioavailability of poorly water-soluble drugs. In particular, whey proteins have shown to be promising co-formers and amorphous stabilizers in ASD formulations, including at high drug loading. In this study, the feasibility of the whey protein β-lactoglobulin (BLG) as a co-former in ASDs was compared to the more traditional ASD co-formers based on synthetic polymers (hydroxypropyl methylcellulose acetate succinate and Eudragit® L) as well as to a nanocrystalline formulation. The poorly water-soluble drug rifaximin (RFX) was chosen as the model drug. All drug/co-former formulations were prepared as fully amorphous ASDs by spray drying at 50% (w/w) drug loading. The BLG-based ASD had the highest glass transition temperature and showed a faster dissolution rate and higher drug solubility in three release media with different pH values (1.2, 4.5, and 6.5) compared to the polymer-based ASDs and the nanocrystalline RFX. In conclusion, BLG is a promising co-former and amorphous stabilizer of RFX in ASD formulations, superior to the selected polymer-based ASD systems or the nanocrystalline formulation.